Pengaruh Corporate Governance Terhadap Nilai Pasar Saham di Pasar Modal - Putri Kemala Dewi Lubis; Fera Daniaty Nababan; Maria Audina Rumapea; Teresia Reginanta Ginting; Yefoni Valentina Banjar (AKUNTANSI 45, 2024)
This research aims to determine the influence of corporate governance on share market value in the capital market. The research results show that corporate governance has a significant influence on stock market value. The results of the analysis show that corporate governance has a significant positive influence on stock market value. The results of this research contribute to capital market theory and practice, as well as providing useful information for investors and capital market policy developers, and overall, the implementation of good corporate governance practices can increase the company's credibility and value in the eyes of investors, thereby increasing stock prices. higher.